Mandibular bone changes and dental status: A radiomorphometric study by the mandibular cortical index on a Senegalese female population aged 40 years and over - Binetou Catherine Gassama; Mamadou Lamine Ndiaye; Papa Abou Lecor; Sarietou Diop; Babacar Toure (Elsevier, 2021)
Introduction: A panoramic radiography is a test, which allows the evaluation of the maxillo-mandibular anatomy. The objective of this study was to use panoramic radiography to evaluate the state of the mandibular basilar cortical of normal tooth and edentulous female subjects over 40 years of age by the mandibular cortical index. Research methods and materials: This was a cross-sectional study of female subjects aged 40 years and over. A sample size of 360 radiographs of 180 totally edentulous and 180 normal tooth subjects were considered for this study. The mandibular basilar cortical bone was assessed by the mandibular cortical index using the classification described by Klemetti: C1 (normal cortex), C2 (slightly or moderately eroded cortex), C3 (severely eroded cortical layer). Statistical data collection and analysis were conducted with Jamovi. The results for qualitative variables were expressed in percentages and those of quantitative variables in means ± standard deviation. The significance level was set at p ≤ 0.05. Results: The average age for normal tooth subjects was 55 ± 11 years. Subjects with C1 CMI represented 27.8% of the population studied, 55.3%, and 16.9% for C2 and C3 indices respectively. The association between MCI and dental status revealed a significant statistical difference p < 0.05. Edentulism is a predictive factor of basilar cortical status after results analysis of polynomial logistic regression Conclusion: This study shows that age combined with dental status are factors affecting the mandibular bone changes investigated by the MCI.